GAMBARAN RELIGIOUS COMMITMENT, SELF-ESTEEM, DAN KEPUASAN HIDUP BERDASARKAN TIPE ARRANGED- MARRIAGE PADA WANITA KETURUNAN ARAB BAALWY - Syihab, Aisyah; Vinaya, Vinaya (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
Abstract — This study aims to describe the religious commitment, self-esteem, and satisfaction with life based on the types of arranged-marriage (low arranged-marriage and high-arranged-marriage) on Arabic Baalwy women. This research was conducted with two approaches, a quantitative approach with 103 female participants (age ranging from 20 to 74 years old) and qualitative approach on 9 participants of the samples. The instruments used for this research were RCI-10 (Religious Commitment Inventory), Self-Esteem Scale, Satisfaction with Life Scale, and interview guidelines. All participants were married by way of an arranged-marriage, either one of the two types of arranged-marriage. The first type (low arranged-marriage) still allows freedom to prospective female partners to accept or decline the male who was betrothed to her, while the second type (high-arranged-marriage) do not give these freedoms. The type was assessed with Arranged-marriage questionnaire that consisted of a close-ended question about the types of arranged-marriage and one open-ended question to ensure the participants’ answers. The results showed that in general the level of religious commitment, self-esteem, and satisfaction with life is quite high. The results indicated that there is no significant differences between religious commitment, self-esteem, and satisfaction with life for both types of arranged-marriage. Based on the qualitative analysis, participants had no objections with their types of arranged-marriage. It was because of their obedience to their parents and God; to maintain the purity of their offspring, so that they do not lose their self-esteem within the group; and they are satisfied with the life they lead. Suggestions for further research is to explore other psychological variables in the group of Arabic Baalwy women.   Abstrak — Penelitian ini bertujuan untuk mengetahui gambaran religious commitment, self-esteem, dan satisfaction with life berdasarkan tipe arranged-marriage (low arranged-marriage dan high arranged-marriage) pada wanita keturunan Arab Baalwy. Penelitian ini dilakukan dengan dua pendekatan, yaitu pendekatan kuantitatif pada 103 partisipan (dari usia 20 sampai 74 tahun), dan pendekatan kualitatif pada 9 orang dari sampel tersebut. Alat ukur yang digunakan adalah RCI-10 (Religious Commitment Inventory), Self-Esteem Scale , Satisfaction with Life Scale , serta pedoman wawancara. Semua partisipan menikah dengan cara dijodohkan, hanya saja terdapat dua tipe perjodohan. Tipe pertama (low arranged-marriage) adalah perjodohan yang masih memberikan kebebasan untuk calon pasangan perempuan menerima atau tidak pria yang dijodohkan kepadanya, sedangkan tipe kedua (high arranged-marriage) tidak memberikan kebebasan tersebut. Tipe perjodohan ini diketahui dari Arranged-marriage questionnaire yang terdiri atas satu pertanyaan tertutup mengenai tipe perjodohan dan satu pertanyaan terbuka untuk memastikan jawaban partisipan. Hasil penelitian menunjukkan bahwa pada umumnya tingkat religious commitment, self-esteem, dan satisfaction with life yang cukup tinggi. Hasil analisis kuantitatif mendapatkan perbedaan tingkat religious commitment, self-esteem, dan satisfaction with life pada kedua tipe arranged-marriage itu tidak signifikan. Berdasarkan hasil analisis kualitatif, partisipan-partisipan tidak merasa keberatan dengan apa pun tingkat perjodohan yang mereka alami. Hal tersebut disebabkan bentuk ketaatan mereka terhadap orangtua dan Tuhan; untuk menjaga kemurnian keturunan mereka, agar mereka tidak kehilangan harga diri dalam kelompok mereka; serta mereka puas dengan kehidupan yang mereka jalani tersebut. Saran untuk penelitian selanjutnya adalah menggali variabel psikologis lainnya pada kelompok wanita Arab Baalwy ini.Abstract— This study aims to describe the religious commitment, self-esteem, andsatisfaction with life based on the types of arranged-marriage (low arranged-marriage andhigh-arranged-marriage) on Arabic Baalwy women. This research was conducted with twoapproaches, a quantitative approach with 103 female participants (age ranging from 20 to74 years old) and qualitative approach on 9 participants of the samples. The instrumentsused for this research were RCI-10 (Religious Commitment Inventory), Self-Esteem Scale,Satisfaction with Life Scale, and interview guidelines. All participants were married by wayof an arranged-marriage, either one of the two types of arranged-marriage. The first type(low arranged-marriage) still allows freedom to prospective female partners to accept ordecline the male who was betrothed to her, while the second type (high-arranged-marriage)do not give these freedoms. The type was assessed with Arranged-marriage questionnairethat consisted of a close-ended question about the types of arranged-marriage and oneopen-ended question to ensure the participants’ answers. The results showed that in generalthe level of religious commitment, self-esteem, and satisfaction with life is quite high. Theresults indicated that there is no significant differences between religious commitment,self-esteem, and satisfaction with life for both types of arranged-marriage. Based on thequalitative analysis, participants had no objections with their types of arranged-marriage.It was because of their obedience to their parents and God; to maintain the purity of theiroffspring, so that they do not lose their self-esteem within the group; and they are satisfiedwith the life they lead. Suggestions for further research is to explore other psychologicalvariables in the group of Arabic Baalwy women.